Synthesis of Nitrogen‐doped Carbon Nanocoils via One‐step Acetonitrile Catalytic CVD using a Ni‐Fe Layered Double Hydroxide as Catalyst Precursor1. Issue 10 (31st October 2013) - Iwasaki, Tomohiro; Tomisawa, Masashi; Nakamura, Hideya; Watano, Satoru
Abstract : A simple catalytic CVD method for the synthesis of N‐doped carbon nanocoils (CNCs), using acetonitrile as both the carbon and nitrogen source, is developed. A Ni–Fe layered double hydroxide that has not been subjected to any prior annealing or reducing treatment is used as a catalyst precursor. The steps of precursor‐to‐catalyst transformation, catalyst activation, deposition of CNCs, and nitrogen doping are performed in situ, in a single process.